Effect of surface anodization on stability of orthodontic microimplant - Karmarker, Sanket (Korean Association of Orthodontists, 2012)
OBJECTIVE: To determine the effect of surface anodization on the interfacial strength between an orthodontic microimplant (MI) and the rabbit tibial bone, particularly in the initial phase after placement. METHODS: A total of 36 MIs were driven into the tibias of 3 mature rabbits by using the self-drilling method and then removed after 6 weeks. Half the MIs were as-machined (n = 18; machined group), while the remaining had anodized surfaces (n = 18; anodized group). The peak insertion torque (PIT) and the peak removal torque (PRT) values were measured for the 2 groups of MIs. These values were then used to calculate the interfacial shear strength between the MI and cortical bone. RESULTS: There were no statistical differences in terms of PIT between the 2 groups. However, mean PRT was significantly greater for the anodized implants (3.79 ± 1.39 Ncm) than for the machined ones (2.05 ± 1.07 Ncm) (p < 0.01). The interfacial strengths, converted from PRT, were calculated at 10.6 MPa and 5.74 MPa for the anodized and machined group implants, respectively. CONCLUSIONS: Anodization of orthodontic MIs may enhance their early-phase retention capability, thereby ensuring a more reliable source of absolute anchorage.